Protection Reversible Data Hiding in Encrypted Images by Distributing Memory before Encryption - Jambhulkar, Sonali; Dudhe, Priyanka (International Journal of Computer Sciences and Engineering, 2025)
Electronic image and data inserting framework have number of critical interactive media applications. Now a days, consideration is paid to reversible data hiding (RDH) in encoded images is more, since it maintains the highest quality property that the original cover can be losslessly recovered after inserted data is extracted while securing the image content’s confidentiality. RDH is a technology used to hide data inside image for high security and can fully recover the original image and private data . All earlier methods fixed data by reversibly vacating room from the encrypted images, which may result to some errors on data extraction and/or image restoration. In this paper, we put forward another method in which we simply encrypt an image without its header by using our new technique. Hence it is easy for the data hider to reversibly fixed data in the encrypted image. The projected technique can achieve real reversibility, that is, data extraction and image recovery are free of any error.